Evidence-based early stage type 2 diabetes follow-up in Belgian primary care practices: Impact of multi-professional teams and care protocols - Matthys, Evi (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2021)
• Multidisciplinary care and guideline follow-up improve type 2 diabetes care. • There is insufficient clinical lifestyle monitoring during type 2 diabetes follow-up. • Practice nurses in primary care improve clinical parameter and lifestyle follow-up. • A discrepancy remains between care protocols and provided type 2 diabetes care. • Self-developed protocol follow-up improves diabetics’ clinical lifestyle monitoring.